Sistem Pembayaran Mixed Method INA-CBGs dan Global Budget di Rumah Sakit: Tahap 1 Uji Coba Mixed Method INA-CBGs-Global Budget di Indonesia - Idris, Fachmi; Nurwahyuni, Atik; Baros, Wan Aisyiah (Jurnal Ekonomi Kesehatan Indonesia, 2020)
When it comes to provider payment system, no one shoe fits all including DRG payment system which in Indonesia are known as INA-CBGs. In some countriesthat used DRGhave mixed it with Global Budget in various mechanisms to maintain the sustainability of the national health insurance system in their countries. BPJS Kesehatan initiated a three-stage pilot study on the implementation of the mixed-method hospital payment system INA-CBGs and Global Budget starting in 2018. The first stage is the Non-Risk stage which aims to test the accuracy of the global budget calculation and prediction and to identify the challenges faced when the mixed-method payment is implemented. The pilot was conducted in 5 districts in 30 hospitals. Initial results show that the calculation and prediction method is accurate to predict the actual hospital claims in the following year. The calculation of the global budget at the district level is more accurate than the hospital level because it accommodates patient transfer from one hospital to another due to changes in hospital capacity. Changes in hospital capacity in the current year and the COVID-19 pandemic requires some adjustments to the budget calculation.